Prophylaxis of complications after radical operations in patients, suffering a mammary gland cancer - Yu. O. Vinnyk; V. G. Vlasenko; A. V. Baranova (Клінічна хірургія, 2019)
Objective. Elaboration of prophylactic measures for complications after radical operations in patients, suffering mammary gland cancer, and estimation of its efficacy.